Development of arc suppression technique for reactive magnetron sputtering - Dudin, S.V.; Farenik, V.I.; Dahov, A.N.; Walkowicz, J. (Физическая инженерия поверхности, 2005)
The technique of arc suppression on the target surface of magnetron sputtering system during reactive deposition of Al₂O₃ coatings has been developed. Damping of arcs is achieved by transient polarity change of the magnetron voltage by means of a simple circuit consisting of a capacitor and an inductive coil. Practically 100% arc inhibition probability is achieved during 5 - 20 мS after its ignition. The energy input into arc before its disappearance is about 50-100 mJ. Results of experimental and theoretical investigations of the arc suppression phenomenon are presented. Process of the magnetron discharge transition to stationary state after the arc suppression has been studied too. Relaxation oscillations of current and voltage accompanying this process are described. A theoretical model of the non-stationary magnetron discharge is developed featuring its dynamic properties. Magnetron discharge dynamic impedance is found.